ASSESSMENT OF SOME ROLL BACK MALARIA INTERVENTION MEASURES ON PATIENTS ATTENDING AHMADU BELLO UNIVERSITY TEACHING HOSPITAL, ZARIA-NIGERIA - Osagiede, Nicholas Osazuyi; Yayock, H. C. (FUDMA Journal of Sciences, 2024)
Malaria is one of the common debilitating diseases in Nigeria. Thus, an assessment of roll back malaria intervention measures on patients attending GOPD clinic of ABUTH Zaria was conducted. A total of 650 Blood samples were collected and examined for malaria parasites. Research on methods of physical and chemical protection was investigated, the use of aerosol insecticide was most popular whereas the use of bed nets had least exposure risk to mosquitoes with a PAR Value (-1.63). The use of prophylactic measures was not significantly associated with malaria prevalence. There was a significant difference between malaria prevalence in individuals that did malaria blood test and those that did not (p<0.05). Of all the preventive measures used in malaria control, Insecticide Treated Nets (ITNS) were least known; only 27.5% of the individuals studied knew about them. It is suggested that the improper use of personal/ preventive measures probably led to the high prevalence of malaria. It is recommended that enlightenment control campaigns on the protective role of ITNS against mosquitoes be stepped up, as ITNS provide a remarkable degree of protection against malaria.